Chloride Fertilization’s Impacts on Kansas Winter Wheat Grain Yield During 2021-2022 - Luiz O. Pradella; Jorge R. Soler; Romulo P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2023)
Previous work suggests that wheat can respond to chloride fertility in Kansas and other regions, but this response depends on Cl availability and the wheat variety. In this study, we aimed to identify and quantify the effects of chloride fertilizer application in different areas and winter wheat varieties across Kansas. Sixteen field experiments were conducted during the 2021–2022 growing season. All experiments were conducted in a split-plot design with Cl fertility levels as whole plot (0 or 20 lb Cl/a) and wheat variety as subplots, with either three or four replicates. One protocol evaluated 24 winter wheat varieties in three locations, while the second protocol evaluated two winter wheat varieties in 13 locations. Chloride fertilization occurred using ammonium chloride and the remaining N rate was applied as urea so that it was not limiting for grain yield. Fertilizer applications occurred in the spring, at the end of the tillering stage (Feekes 4). At all experiments, two fungicide applications (Feekes 7 and 10.5) ensured that diseases were not a confounding factor. Across experiments and treatments, total available Cl ranged from 13 to 63 lb/a, and grain yield ranged from 35 to 92 bushels per acre. The results of these 16 experiments predominantly suggested that the wheat variety × location interaction determined wheat yield, only with trends of Cl fertilization effect (P<0.08). Chloride available between soil supply and fertilizer applied was associated positively with chloride concentration in the wheat biomass tissue at anthesis, and had an exponential rise to maximum relationship with relative grain yield. These results are constrained to a single growing season, but showed a limited potential benefit of Cl fertilization under the studied soil and weather conditions. Expanding the study to locations with less available Cl at sowing, or greater precipitation amounts, could likely increase the chances of finding positive results for Cl fertilization.
Keywords: wheat; varieties; chloride; fertilizer; biomass; ammonium chloride